Responding to Natural Disasters With Disaster Risk Reduction and Management - Meredith DeCock-Caspell (The University of Alabama, 2021)
A review of the book: Vinrod Thomas, Climate Change and Natural Disasters: Transforming Economies and Policies for a Sustainable Future. Routledge, 2017, 184 pages. ISBN: 9781412864404